First Source to Gymnastics : Rules, Equipment, and Key Routine Tips - Maurer, Tracy Nelson 1965 (North Mankato, Minnesota Capstone Press, a Capstone imprint, 2018)
Shows kids the world of gymnastics. From equipment to training tips and scoring rules, kids will be excited by stunning photographs of gymnasts and engaging text.
Includes bibliographical references (page 23) and index
Age 6-9